Achtsamkeit. Zur pädagogischen Relevanz einer Technik der Selbstsorge (im Erscheinen) - Engel, Juliane; Göhlich, Michael (Technik, 2017)

Beratung im Kontext des Strukturwandels. Wirkung(en) von Beratung im Übergang - Althans, Birgit; Lamprecht, Juliane (Beratung im Übergang : zur sozialpädagogischen Herstellung von biographischer Reflexivität, 2013)

Bilder, Räume, Praktiken – Potentiale der Ethnographie für eine sozialpädagogische Evaluationsforschung - Althans, Birgit; Lamprecht, Juliane (Feld und Theorie : Herausforderungen erziehungswissenschaftlicher Ethnographie, 2012)

Bildsprache – Sprachbilder: Eine empirische Studie zu neuen Führungskulturen im Übergang vom Elementar- in den Primarschulbereich - Engel, Juliane (Erziehungswissenschaftliche Perspektiven in frühpädagogischer Theoriebildung und Forschung, 2015)

Bildung und Bewertung – zu Möglichkeitsräumen in responsiven Evaluationen - Lamprecht, Juliane (Qualitative Bildungsforschung und Bildungstheorie, 2012)

"C'est épiusant, l'Europe" - L'integration européene entre illusion et practique - Blaschke, Gerald; Lamprecht, Juliane; Wulf, Christoph; et al. (La citoyenneté européenne : Désirs d'Europe : Regards des marges, 2011)

Cultural identity in multilocal spaces - Engel, Juliane; Fritzsche, Bettina (Diaspora, Indigenous, and Minority Education, 2019)
The vast differences in how spaces can be perceived and scientifically examined have long been a central topic in education science, and not only since the spatial turn (Löw 2011, Schroer 2018, Glaser et al. 2018, Pardo/Patro 2018). In order to unlock the wide range of diverse perspectives on spaces, in this special issue we seek to build and review the learning and education theory potential of multilocal points of access. What can be learned if one assumes spaces to be multilocal and asks, for example, how the different cultures of family spaces can be, which atmospheres they shape for the different members of the family, or how they arise through co-present, or even virtual or imaginative, relationing? In this case, multilocality appears, for example, as a family practice of connecting very different, individual locations. We are then interested in investigating how a childhood can be examined as a passing through of diverse spaces, as well as initial attempts to design one’s own spaces, for example by building ‘dens’ in corn fields or in nursery spaces. One can also ask how children use, or find new uses for, the social spaces of adults. Here, multilocality unlocks access to the simultaneity of different spatial structures in the same location. Although it also occurs at an earlier age, it is when children reach school in particular that one can observe how differently the same locations can be/are entered into, and social differences (re)produced. The same classroom is home to very different students with very different starting points in schooling. Not all individuals know how to position themselves in a space in such a way that their positioning is recognised and thus accepted by society. Consequently, although all the students are being taught in the same place, not all are sitting in the same classroom. Another multilocal space, the university, also often fails to offer a shared place of different thinking, it could be characterised by its diversity of possible perspectives and thus different location dependencies and reflections thereon.
CRIS-Team Scopus Importer:2019-05-14

Cultural Sedimentations - Ethnography on the Materiality and Historicity of Aesthetic Practices - Engel, Juliane; Beach, Dennis; Jörissen, Benjamin (Routledge, 2020)
The importance of materiality in learning and education processes has been emphasized in numerous empirical studies and theoretical argumentation figures, dating from both before and after the material turn. Therefore, it is evident to take the dimensions of material characteristics, structures and properties, cultural historical inscriptions as well as modern design processes, and spatial arrangements (e.g. architectures and environments) into account. As most objects and material surroundings of our everyday life have been conceived for a special use, we have to deal with their pre-designed structures and their historical dimensions. Even if we alienate them from their original purpose, the cultural sedimentations leave (in-)visible traces in our (aesthetic) practices as well as our practices deposit new sediments. But of course, materialities of education need to be discussed in the context of global(ising) capitalism, education justice and equity through ethnographies of education experiences. Therefore, (meta-)ethnographies on race, space and class history will take place in our discussions. Against this background, we focus on the historicity of materiality and relational practices and how both may influence, produce and generate each other. In this context we question how the historicity of materiality articulates itself in relational practices and how people experience the historicity inscribed into the material form for instance of images, poems, performances and buildings. By asking questions like these we strive to open up two mainly theoretical (Section 1), two methodological (Section 2) and five mainly empirical approaches (Section 3) towards aesthetic practices as relational education processes (see Table of Contents). The ethnographies are situated in arts and museum education, school, post-digital and youth culture, studies of design and new maker culture.
Keywords: aesthetics; aesthetic education; aesthetic practice; materiality; material turn; ethnography; qualitative research; education

Das Geheimnis „guter“ Praxis. Qualitative Evaluationsforschung im sozialpädagogischen Feld - Lamprecht, Juliane (Empirische Forschung in der sozialen Arbeit : Methoden und methodologische Herausforderungen, 2012)

Das 'Unterleben in der Pause' aus der Perspektive der Praxeologischen Wissenssoziologie. Eine dokumentarische Videointerpretation (im Erscheinen) - Engel, Juliane; Bohnsack, Ralf (Seen from different perspectives. Interdisziplinäre Videoanalyse: Rekonstruktionen einer Videosequenz aus unterschiedlichem Blickwinkel, 2017)

Digitalität in der Schulkultur - Jörissen, Benjamin; Engel, Juliane (2023)

Digitalität in der Schulkultur - Jörissen, Benjamin; Engel, Juliane (Schüler, 2023)

Einleitung - Engel, Juliane; Althans, Birgit (Responsive Organisationsforschung. Methodologien und institutionelle Rahmungen von Übergängen, 2016)

Erkenntnis, Reflexion und Bildung – zur Frage neuer Formen der Archivierung, Bereitstellung und Nachnutzung von Forschungsdaten - Engel, Juliane; Demmer, C.; Fuchs, T. (Zeitschrift für Erziehungswissenschaft, 2020)

Erwartungshorizonte und Handlungspraxis - zu einem produktiven Spannungsverhältnis für responsive Evaluationsstudien im Bereich der Frühpädagogik - Lamprecht, Juliane (Zeitschrift für Evaluation, 2013)

ErzieherInnen und LehrerInnen im Austausch. Videoanalysen zur Sinnkomplexität interaktiver Körperlichkeit - Lamprecht, Juliane (Dokumentarische Video- und Filminterpretation: Methodologie und Forschungspraxis, 2014)

"Europa ist anstrengend" - zwischen Wunschbild und Praxis europäischer Integration - Engel, Juliane; Wulf, Christoph; Blaschke, Gerald (Europäische Bürgerschaft in Bewegung, 2011)

Evaluation als Erfahrung - Lamprecht, Juliane (Erfahrung - Erfahrungen, 2012)

Evaluation als Methode organisationspädagogischer Praxis (im Erscheinen) - Engel, Juliane (Handbuch Organisationspädagogik, 2017)

Evaluation in der Sozialen Arbeit im Spannungsfeldvon Forschung, Steuerung und Entwicklung - Althans, Birgit; Lamprecht, Juliane (Standpunkt: sozial : Hamburger Forum für Soziale Arbeit und Gesundheit, 2010)

Evaluation und Imagination - Lamprecht, Juliane (Dokumentarische Evaluationsforschung : theoretische Grundlagen und Beispiele aus der Praxis, 2010)

Geburt – ein familiales Ereignis? - Engel, Juliane; Foltys, Julia (Geburt in Familie, Kliniken und Medien. Eine qualitative Studie, 2008)

Geburt in Familie, Kliniken und Medien. Eine qualitative Studie - Engel, Juliane; Wulf, Christoph; Althans, Birgit; Foltys, Julia; Fuchs, Martina; Klasen, Sigrid; Tegethoff, Dorothea (Budrich, 2008)

Geburt und Familie - Engel, Juliane; Foltys, Julia (Das Imaginäre der Geburt. Praktiken, Narrationen und Bilder, 2008)

Glokalisierte Klassenräume? ‚Doing Ethics‘ als Bearbeitung von Ungewissheit - Engel, Juliane; Göhlich, Michael; Möller, Elke; Stiftinger, Sophia (Zeitschrift für interpretative Schul- und Unterrichtsforschung, 2021)

Haltungen - Perspektiven der qualitativen Bildungs- und Biographieforschung - Engel, Juliane; Demmer, Christine; Fuchs, Thorsten; Jörissen, Benjamin; Wiezorek, Christine (Haltungen: Zugänge aus Perspektiven qualitativer Bildungs- und Biographieforschung, 2023)

Image language and the language of images: A closer examination of videography in cross-cultural school studies - Engel, Juliane (Research in Comparative and International Education, 2015)

Implizite Geschlechter-Inszenierung und Professionskulturen. Zu aktuellen Optimierungsbestrebungen beim Übergang von Kita zur Grundschule - Lamprecht, Juliane; Althans, Birgit; Freis, Manuel (Erziehung, Bildung und Geschlecht : Männlichkeit im Fokus der Gender-Studies, 2012)

Implizites Wissen im interdisziplinären Diskurs - Engel, Juliane; Paul, Heike (Handbuch Schweigendes Wissen: Erziehung, Bildung, Sozialisation und Lernen, 2017)
Keywords: implizites Wissen

Interaction, subalternity, and marginalisation: An empirical study on glocalised realities in the classroom - Engel, Juliane; Göhlich, Michael; Möller, Elke (Diaspora, Indigenous, and Minority Education, 2019)
Using empirical examples from our research project “Glocalised Living Environments” (funded by the German Research Foundation, DFG), this contribution emphasises the difference between acting in an ethical-rational and in an ethical-performative way. Videos from schools in Southern Germany allow us to elaborate cultural identity and its genesis in practices of marginalisation and minorization in the classroom. In the 21st century, the worlds we live in are no longer bound to homogeneous conceptions of sense, meaning, and interpretations within a common normative sphere. They are scattered, linked across the globe, and dis-located in reality and virtuality. In short, the world and our worlds are genuinely multilocal and “glocalised.” The formation of cultural identities within this setting is of particular educational interest, as it demonstrates that differences in power, empowerment attempts, isolation, and exclusion happen on a basic level, even where cooperation has been assumed and global equity has been foregrounded.
CRIS-Team Scopus Importer:2019-08-13

Introduction: cultural sedimentations–ethnography on the materiality and historicity of aesthetic practices - Engel, Juliane; Beach, Dennis; Jörissen, Benjamin (Ethnography & Education, 2020)
CRIS-Team Scopus Importer:2020-04-17

Organisationale Grenzgänger? Professionelle Akteure in internationalen Kooperationen - Engel, Juliane; Althans, Birgit (Organisation und kulturelle Differenz. Diversity, Interkulturelle Öffnung, Internationalisierung, 2013)

Pädagogische Blicke zwischen inneren und äußeren Bildern - Engel, Juliane (Pädagogische Blicke, 2016)

Praxis, Praktiken und Praktikum – forschungsmethodische Zugänge zu Feldern der Sozialpädagogik und Pädagogik der frühen Kindheit - Althans, Birgit; Lamprecht, Juliane (Konsens und Kontroversen - Sozialpädagogik und Pädagogik der frühen Kindheit im Dialog, 2013)

Rekonstruktive Responsivität - Zum Begriff des Wissens in der dokumentarischen Evaluationsforschung - Kubisch, Sonja; Lamprecht, Juliane (Dokumentarische Methode. Grundlagen - Entwicklungen - Anwendungen, 2013)

Rekonstruktiv-responsive Evaluation in der Praxis : neue Perspektiven dokumentarischer Evaluationsforschung - Lamprecht, Juliane (VS-Verl., 2012)

Responsive Evaluation: Partizipative Initiierung organisationalen Lernens - Lamprecht, Juliane (Organisation und Partizipation. Beiträge der Komission Organisationspädagogik, 2013)

Responsive Studien als ästhetische Resonanzräume - Engel, Juliane; Althans, Birgit (Responsive Organisationsforschung. Methodologien und institutionelle Rahmungen von Übergängen, 2016)

Schule und Medialität - Jörissen, Benjamin; Engel, Juliane (Handbuch Schulforschung, 2022)
Der Beitrag eröffnet medialitätstheoretische Perspektiven auf aktuelle Lern- und Bildungsprozesse im Kontext schulischer Digitalisierung. Am Beispiel der Medialität von Schul- und Unterrichtsräumen wird die Hervorbringung (neuer) Lehr-Lernsubjektivationen analysiert und es werden gegenwärtige Formen (post)digitaler Relationierung befragt. So lassen sich die Datafizierung und Algorithmisierung von Erziehung, Bildung und Individualität auch jenseits westlich-idealistischer Konstruktionen „souveräner Subjektivität“ reflektieren und der Medialität relationaler Subjektvierung nachgehen.
Keywords: Bildung; Schule; Medialität; Digitalität; Subjekt und Kritik

Sozial’no-pedagogičeskie idei v sovremennoj evropejskoj teorii i praktike: sbornik naučnych statej/ Nauč - Engel, Juliane (Sozial-pedagogische Ideen in der gegenwärtigen europäischen Theorie und Praxis: Sammelband wissenschaftlicher Aufsätze, 2011)

Spectra of Transformation - Jörissen, Benjamin; Unterberg, Lisa; Klepacki, Leopold; Engel, Juliane; Flasche, Viktoria; Klepacki, Tanja (Waxmann, 2018)
Like every pedagogical field, the fields of aesthetics, arts and cultural education have been confronted with various transformational dynamics in recent decades. Transformation processes such as globalization, digitization or transculturalization not only characterize a change in social and cultural framework conditions, but also lead to changes in self-understanding, working methods, contents, and objectives in the research of these educational fields. The anthology "Spectra of Transformation" gathers a variety of perspectives on the question of the research on aesthetics, artistic and cultural education, which were discussed by international participants and speakers at the Winter School 2017 in Nuremberg.<br

The materiality of biographical knowledge – ethnography on aesthetic practices. - Engel, Juliane (Ethnography & Education, 2020)

The potential of videography in comparative education: Introduction - Engel, Juliane; Fritzsche, Bettina (Research in Comparative and International Education, 2015)

Transgressive Videography – Videographic Access to Practices of Subjectivisation between Materiality, Mediality, and Aesthetics (im Erscheinen) - Engel, Juliane; Jörissen, Benjamin; Klepacki, Tanja; Möller, Elke (Oxford Encyclopedia of Qualitative Research Methods in Education, 2021)

"...und jetzt hast de det größte Projekt überhaupt an ner Backe". Mutterschaftsrepräsentationen zwischen Beruf und Familie - Engel, Juliane (Geburt in Familie, Kliniken und Medien. Eine qualitative Studie, 2008)

Unsichtbare Sichtbarkeiten. Kontrollverlust und Kontrollphantasmen in öffentlichen und jugendkulturellen Digitalisierungsdiagnosen - Engel, Juliane; Jörissen, Benjamin (Gegenwartsdiagnosen, 2019)

Urteilsbildung und Einbildungskraft. Zum Fremden im Geographieunterricht - Engel, Juliane; Ulrich, Marie (Urteilen lernen II. Ästhetische, politische und eschatologische Perspektiven moralischer Urteilsbildung im interdisziplinären Diskurs, 2014)

Wirkungsorientierung in der Jugendberufshilfe – wer macht die Unterschiede? - Lamprecht, Juliane (Soziale Arbeit und Geschlecht : Herausforderungen jenseits von Universalisierung und Essentialisierung, 2012)

Zeitlichkeit und Materialität. Interdisziplinäre Perspektiven auf Theorien und Phänomene der Präsenz - Kirchmann, Kay; Engel, Juliane; Gebhardt, Mareike (2019)

Zu glokalisierenden Praktiken ethischen Urteilens in Schule und Unterricht. - Engel, Juliane; Applis, Stefan; Mehren, Rainer (Zeitschrift für internationale Bildungsforschung und Entwicklungspädagogik, 2020)

Zur materiellen Relationalität von Lernprozessen in Lernwerkstätten - Engel, Juliane; Klepacki, Leopold (Perspektiven auf Hochschullernwerkstätten. Wechselspiele zwischen Individuum, Gemeinschaft, Ding und Raum, 2019)

Zur Pluralisierung der Lebenswelt und einer Individualisierung der Lebensführung als Arbeit am Selbst. Eine empirische Studie zu Übergängen - Engel, Juliane; Althans, Birgit (Grenzen und Lebenslauf. Beratung als Form des Managements biographischer Übergänge, 2014)

Zur (Un-)Sichtbarkeit organisationalen Lernens. Theoretische Überlegungen - Engel, Juliane (Organisation und Theorie. Beuträge der Kommission Organisationspädagogik, 2016)